2017
DOI: 10.1111/een.12400
|View full text |Cite
|
Sign up to set email alerts
|

Elevationally biased avian predation as a contributor to the spatial distribution of geometrid moth outbreaks in sub‐arctic mountain birch forest

Abstract: 1. Population dynamics and interactions that vary over a species' range are of particular importance in the context of latitudinal clines in biological diversity. Winter moth (Operophtera brumata) and autumnal moth (Epirrita autumnata) are two species of eruptive geometrids that vary widely in outbreak tendency over their range, which generally increases from south to north and with elevation. 2. The predation pressure on geometrid larvae and pupae over an elevational gradient was tested. The effects of backgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The rates of pupal mortality from predators were overall similar to those found in prior studies in British Columbia (Horgan et al, 1999; Horgan & Myers, 2004; Roland, 1988) and Nova Scotia (Macphee et al, 1988; Pearsall & Walde, 1994), but only for the lower density years following C. albicans establishment at these sites (Roland, 1994). The predation rates we recorded were similar to those reported from western Europe (Hansen et al, 2009; Heisswolf et al, 2010; Varley et al, 1973), but were higher than some other estimates of pupal mortality in northern Europe from outbreak winter moth populations or high elevation sites (Klemola et al, 2009, 2014; Pepi et al, 2017). This further supports that idea depicted in Figure 1 that, at high densities, the predator saturation point can be surpassed resulting in relatively low predation rates.…”
Section: Discussionsupporting
confidence: 87%
“…The rates of pupal mortality from predators were overall similar to those found in prior studies in British Columbia (Horgan et al, 1999; Horgan & Myers, 2004; Roland, 1988) and Nova Scotia (Macphee et al, 1988; Pearsall & Walde, 1994), but only for the lower density years following C. albicans establishment at these sites (Roland, 1994). The predation rates we recorded were similar to those reported from western Europe (Hansen et al, 2009; Heisswolf et al, 2010; Varley et al, 1973), but were higher than some other estimates of pupal mortality in northern Europe from outbreak winter moth populations or high elevation sites (Klemola et al, 2009, 2014; Pepi et al, 2017). This further supports that idea depicted in Figure 1 that, at high densities, the predator saturation point can be surpassed resulting in relatively low predation rates.…”
Section: Discussionsupporting
confidence: 87%
“…Our data from six elevational gradients, in combination with other studies addressing the effects of elevation on plant-feeding insects and insect herbivory at high latitudes (Kristensen et al, 2020;Mjaaseth et al, 2005;Pepi et al, 2017;Ruohomäki et al, 1997), indicate that an increase in herbivory with elevation is more frequent in Arctic mountains than in mountains at lower latitudes (Moreira et al, 2018). This pattern, which contrasts with both theoretical predictions and the results of the analysis of elevational changes in herbivory in tropical and temperate mountains (Galmán et al, 2018), likely emerges due to an inverse elevational gradient in temperatures at the soil surface between closed-canopy forests and open alpine habitats.…”
Section: Con Clus Ionmentioning
confidence: 93%
“…In subarctic mountain birch forests, defoliation rates are higher during outbreaks in high elevations. Pepi et al [82] showed that predation rates on E. autumnata and O. brumata larvae were almost twice as high in low versus high elevation sites, and that release from predation pressure at high elevations can favor outbreaks in these cooler habitats. It therefore appears that top-down effects can override bottom-up effects of climate warming in some tri-trophic systems.…”
Section: Defoliatorsmentioning
confidence: 99%